ANALYSIS OF FORMATION AND CHARACTERIZATION OF Ni-TiN-AlN COMPOSITE LAYERS USING ELECTRODEPOSITION METHOD WITH PULSE CURRENT DENSITY VARIATIONS: ANALISIS PEMBENTUKAN DAN KARAKTERISASI LAPISAN KOMPOSIT Ni-TiN-AlN DENGAN METODE ELEKTRODEPOSISI TERHADAP VARIASI RAPAT ARUS PULSA - Syamsinar; Esmar Budi; Teguh Budiprayitno (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2025)
In this paper, the formation of a Ni-TiN-AlN composite coating layer is carried out to study the effect of variations in pulse current density on surface morphology and coating composition. The coating process is carried out using the electrodeposition method. The Ni-TiN-AlN composite layer was formed on a Tungsten Carbide (WC) substrate with an electrolyte solution composition consisting of 0.17 M NiCl2.6H2O, 0.38 M NiSO4.6H2O, 0.49 M H3BO3, 0.6 g/l Sodium Dodecyl Sulfate (SDS), particles TiN strengthening powder of 6 gr/l and AlN powder of 10 g/l. Electrodeposition on the substrate was carried out for 30 minutes and variations in current density used were 0.15 mA/mm2, 0.25 mA/mm2, and 0.35 mA/mm2. The Ni-TiN-AlN composite layer was characterized using SEM-EDS (Scanning Electron Microscopy-Energy Dispersive Spectroscopy), X-Ray Diffraction (XRD), and Hardness Test (Vickers). The results show that the surface morphology and composition of the Ni-TiN-AlN composite layer are influenced by the current density used.